Hystera Ektomia: not always called for - Jindal, Manvi; Garg, Swati; Harjai, Rachit; Sharma, Urvashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Unsympathetic hysterectomies have seen a rising trend in India in the recent times, the unsuspecting folks being pushed into surgeries wrongly citing the austerity of the illness. We highlight a case of a 26 year old female patient with post-partum bleeding per vaginum for 6 months, who was initially treated conservatively at several hospitals. Later, histopathologically proven to be a case of Choriocarcinoma (WHO Stage I with FIGO prognostic score of 5), was hysterectomized hastily overlooking the reports and the patient discharged without further intervention. Few months later the patient presented with brain and lungs metastases. Had the patient been properly evaluated and treated appropriately initially, surgery was not indicated. Instead the patient was callously operated upon and histopathological report not followed which resulted in patient developing distant metastases (WHO Stage IV with FIGO prognostic score of 17). Unwarranted and unevaluated hysterectomies should be checked by appropriately evaluating the extent of the disease.